2012
DOI: 10.1210/en.2011-0259
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Enhances Glucokinase Activity in Pancreatic β-Cells through the Association of Epac2 with Rim2 and Rab3A

Abstract: Glucokinase (GK), which phosphorylates D-glucose, is a major glucose sensor in β-cells for glucose-stimulated insulin secretion (GSIS) and is a promising new drug target for type 2 diabetes (T2D). In T2D, pancreatic β-cells exhibit defective glucose sensitivity, which leads to impaired GSIS. Although glucagon-like peptide-1-(7-36)-amide (GLP-1) is known to enhance β-cell glucose sensitivity, the effect of GLP-1 on GK activity is still unknown. The present study demonstrated that GLP-1 pretreatment for 30 min s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…We also found that increasing cAMP levels with forskolin or isobutylmethylxanthine activated the FRET-GCK sensor (Fig. 3I), consistent with previous work tying cAMP levels to GLP-1 activation of GCK (38). The ability of these treatments to affect cAMP levels in ␤TC3 cells was confirmed in cells expressing the ICUE3 cAMP FRET indicator (39) (Fig.…”
Section: Er Casupporting
confidence: 89%
“…We also found that increasing cAMP levels with forskolin or isobutylmethylxanthine activated the FRET-GCK sensor (Fig. 3I), consistent with previous work tying cAMP levels to GLP-1 activation of GCK (38). The ability of these treatments to affect cAMP levels in ␤TC3 cells was confirmed in cells expressing the ICUE3 cAMP FRET indicator (39) (Fig.…”
Section: Er Casupporting
confidence: 89%
“…Such behavior would contribute to the formation of the tripartite Rab3A-RIM1␣-Munc13 complex, which in turn would increase the priming of vesicles to a release-competent state. In support of this hypothesis, Epac proteins activate the small G proteins Rap1 and Rab3A to induce exocytosis in non-neuronal systems (24), whereas Epac2 interacts with RIM2 to promote insulin secretion in a cAMP-dependent, PKA-independent manner in pancreatic ␤ cells (27,45,63).…”
Section: Discussionmentioning
confidence: 89%
“…Epac Activation Enhances the Interaction between Rab3 and RIM Proteins-In non-neuronal preparations, Epac proteins activate small G proteins like Rap1 and Rab3 (24) and then bind to the active zone protein RIM (27,45). Small G proteins cycle between active GTP-bound and inactive GDP-bound states (46).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose uptake by pancreatic b-cells, through the glucose transporter GLUT2 and glucokinase activity, is essential for the normal insulin secretory response to hyperglycemia (35,36). To further ascertain the stimulatory and inhibitory roles of 43RFa and 26RFa, respectively, on GSIS, glucose uptake was determined in INS-1E b-cells and human pancreatic islets.…”
Section: Rfa and 26rfa Both Promote Survival And Inhibit Apoptosis mentioning
confidence: 99%